Opportunities Of Getting Demographic Dividends In Uzbekistan - Mirzakarimova Muyassar Muminovna, Khajiyev Baktiyor (International Journal of Advanced Science and Technology, 2020)
This scientific article is devoted to the research of the peculiarities of the demographic situation in Uzbekistan. In addition, it has identified opportunities to get demographic dividends. Moreover, the article has studied the essence of the demographic dividend and its impact on the economic growth. Basing on the research results the authors have developed scientific proposals and practical recommendations.